Reevaluation of bacteriocinogeny in Neisseria gonorrhoeae. - Knapp, J S (1975)
Bacteriocin typing has been described previously and proposed for typing gonococci. A survey has been made of 150 strains of N. gonorrhoeae from various places to determine the feasibility of a gonocin typing system. All strains were found to produce an inhibitory substance which inhibited all strains of gonococci tested, one strain of Neisseria flavescens, two strains of Neisseria meningitidis, as well as the producing strain itself. The inhibitory activity was enhanced by supplementary glucose, reduced by supplementary serum, and unaffected by the addition of HEPES buffer, by the temperature of incubation, or by the exposure of potential producer strains to sublethal concentrations of mitomycin C. This nonspecific inhibitory activity differed from that of a putative bacteriocin produced by a strain of N. meningitidis, in that the latter inhibited most other meningococci but not the producer strain itself. Bacteriocinogeny has not yet been convincingly demonstrated in N. gonorrhoeae, and gonocin typing has not yet been shown to be feasible. Production of the nonspecific inhibitor may have obscured past attempts to demonstrate type-specific gonococcal bacteriocin.